Hubungan Kebiasaan Sarapan terhadap Status Gizi dan Tingkat Konsentrasi Belajar Siswa di SMP Kemala Bhayangkari 7 Porong Sidoarjo - Nabila Cahya Listiyapuji; Satwika Arya Pratama (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Breakfast is an activity of eating and drinking from waking up until 9am. Breakfast mainly consists of sources of fiber, high protein, and low fat. If breakfast is often left out, it can affect the nutritional status and level of learning concentration in students. The purpose of this study was to identify the correlation of breakfast habits on nutritional status and the level of student learning concentration at Kemala Bhayangkari 7 Porong Sidoarjo Junior High School. The method of this study was quantitative correlation with a crosssectional design. The sample was taken by purposive sampling with the number of samples in this study was 85 students in class VII and VIII who fulfilled the inclusion criteria. The data obtained were statistically tested using the Chi-Square test. Based on the test results that have been conducted, Kemala Bhayangkari 7 Porong Sidoarjo Junior High School students on average had breakfast habits that falls into the occasional category 43.52%, on average had normal nutritional status 56.47%, and the average level of learning concentration was good 57.64%. There was no relationship between breakfast habits and nutritional status of students at Kemala Bhayangkari 7 Porong Sidoarjo Junior High School (p=0.088), and there was a significant relationship between breakfast habits and students' learning concentration at Kemala Bhayangkari 7 Porong Sidoarjo Junior High School (p=0.000).